The Effect of Fatigue Damage on the Force Required to Remove a Restoration in a Cement-Retained Implant System - Darian Kaar, DDS, MSD;1 Yoshiki Oshida, MS, PhD;2 (Journal of Prosthodontics, 2006)
To evaluate the luting agents and retentive forces before and after mechanical stressing